BITE MARKS – A BALANCED PERSPECTIVE - Smith, Joe H; M Singh, (Student's Journal of Health Research Africa, 2024)
The article compliments the recently published manuscript titled “Bite Marks – A Vital Investigation in the Field of Forensic Medicine”. It highlights the importance of bite mark analysis in forensic dentistry for solving crimes. Forensic odonatologists handle dental evidence, which is vital for law enforcement. Although bite marks have historically been used in criminal cases, doubts about their accuracy remain, highlighting the necessity for more uniform methods. Computer-assisted techniques have improved precision, yet obstacles persist in guaranteeing scientific validity and reliability. The President's Council of Advisors on Science and Technology stresses the significance of fundamental validity and standardized procedures. Historical cases show the importance of improving analysis techniques. Ultimately, bite mark evidence is essential in court but should be corroborated by other evidence to ensure accuracy and credibility, emphasizing the importance of cooperation for dependability and validity.